Carnosic Acid Alleviates BDL-Induced Liver Fibrosis through miR-29b-3p-Mediated Inhibition of the High-Mobility Group Box 1/Toll-Like Receptor 4 Signaling Pathway in Rats - Zhang, Shuai; Wang, Zhecheng; Zhu, Jie; Xu, Ting; Zhao, Yan; Zhao, Huanyu; Tang, Fan; Li, Zhenlu; Zhou, Junjun; Gao, Dongyan; Tian, Xiaofeng; Yao, Jihong (Frontiers in Pharmacology, 2018)
Fibrosis reflects a progression to liver cancer or cirrhosis of the liver. Recent studies have shown that high-mobility group box-1 (HMGB1) plays a major role in hepatic injury and fibrosis. Carnosic acid (CA), a compound extracted from rosemary, has been reported to alleviate alcoholic and nonalcoholic fatty liver injury. CA can also alleviate renal fibrosis. We hypothesized that CA might exert anti-liver fibrosis properties through an HMGB1-related pathway, and the results of the present study showed that CA treatment significantly protected against hepatic fibrosis in a bile duct ligation (BDL) rat model. CA reduced the liver expression of α-smooth muscle actin (α-SMA) and collagen 1 (Col-1). Importantly, we found that CA ameliorated the increase in HMGB1 and Toll-like receptor 4 (TLR4) caused by BDL, and inhibited NF-κB p65 nuclear translocation in fibrotic livers. In vitro, CA inhibited LX2 cell activation by inhibiting HMGB1/TLR4 signaling pathway. Furthermore, miR-29b-3p decreased HMGB1 expression, and a dual-luciferase assay validated these results. Moreover, CA down-regulated HMGB1 and inhibited LX2 cell activation, and these effects were significantly counteracted by antago-miR-29b-3p, indicating that the CA-mediated inhibition of HMGB1 expression might be miR-29b-3p dependent. Collectively, the results demonstrate that a miR-29b-3p/HMGB1/TLR4/NF-κB signaling pathway, which can be modulated by CA, is important in liver fibrosis, and indicate that CA might be a prospective therapeutic drug for liver fibrosis. Abbreviations Carnosic acid (CA); High-mobility group box 1 (HMGB1); Toll-like receptor 4 (TLR4); Nuclear factor kappa B (NF-κB); Bile duct ligation (BDL); Alanine aminotransferase (ALT); Aspartate aminotransferase (AST); α-Smooth muscle actin (α-SMA); Collagen 1 (Col-1); Matrix metalloprotein 9 (MMP9); Transforming Growth factor-beta 1 (TGF-β1); Transforming growth factor-beta receptor type 1 (TGF-β R1) Key words: Carnosic acid; Bile duct ligation; High-mobility group box-1; miR-29b-3p; Liver fibrosis